Improving Marketing Performance with Marketing Capability: Service Dominant Logic B2B Export Furniture - Ali, Ali; Arifin, Samsul; Roosdhani, Mohammad Rifqy; Komariyatin, Nurul; Huda, Nurul (Jurnal Entrepreneur dan Entrepreneurship, 2024)
This study aims to enhance marketing capability by increasing customer involvement and marketing innovation to improve marketing performance and develop B2B Service-Dominant Logic (SDL) in furniture export companies. This research employs a quantitative method. The population for this study consists of 307 furniture companies that export. Using the Slovin formula, a sample of 171 furniture export enterprises was obtained. Two sample selection techniques were employed, which were probability sampling and lottery-based simple random sampling. The results of this study indicate that marketing capabilities impact consumer participation and marketing innovation, and that both customer involvement and marketing innovation enhance marketing performance. Theoretical implications suggest the development of a B2B service-dominant logic theory. Marketing capability and customer involvement influence marketing outcomes. Companies must focus on developing improved items and designs for new products. Collaboration with customers has also contributed to improved marketing performance.